A Systematic Review of the Incidence, Prevalence, Costs, and Activity and Work Limitations of Amputation, Osteoarthritis, Rheumatoid Arthritis, Back Pain, Multiple Sclerosis, Spinal Cord Injury, Stroke, and Traumatic Brain Injury in the United States: A 2019 Update - Lo, Jessica; Chan, Leighton; Flynn, Spencer (Archives of physical medicine and rehabilitation, 2021)
To present recent evidence on the prevalence, incidence, costs, activity limitations, and work limitations of common conditions requiring rehabilitation. Medline (PubMed), SCOPUS, Web of Science, and the gray literature were searched for relevant articles about amputation, osteoarthritis, rheumatoid arthritis, back pain, multiple sclerosis, spinal cord injury, stroke, and traumatic brain injury. Relevant articles (N=106) were included. Two investigators independently reviewed articles and selected relevant articles for inclusion. Quality grading was performed using the Methodological Evaluation of Observational Research Checklist and Newcastle-Ottawa Quality Assessment Form. The prevalence of back pain in the past 3 months was 33.9% among community-dwelling adults, and patients with back pain contribute $365 billion in all-cause medical costs. Osteoarthritis is the next most prevalent condition (approximately 10.4%), and patients with this condition contribute $460 billion in all-cause medical costs. These 2 conditions are the most prevalent and costly (medically) of the illnesses explored in this study. Stroke follows these conditions in both prevalence (2.5%-3.7%) and medical costs ($28 billion). Other conditions may have a lower prevalence but are associated with relatively higher per capita effects. Consistent with previous findings, back pain and osteoarthritis are the most prevalent conditions with high aggregate medical costs. By contrast, other conditions have a lower prevalence or cost but relatively higher per capita costs and effects on activity and work. The data are extremely heterogeneous, which makes anything beyond broad comparisons challenging. Additional information is needed to determine the relative impact of each condition.